Challenging health economics - Mooney, Gavin H. (Oxford : Oxford University Press, 2009)
This text mounts a critique of health economics, arguing it has been too dominated by the economics of health care and has largely ignored the impact of poverty, inequality, and lack of education on health. The author proposes a form of collective decision making through communitarianism as a basis for a new paradigm.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Medical economics; Public health -- Economic aspects; Public health -- Political aspects; Medical policy